1999
DOI: 10.1007/s002400050097
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, citrate, magnesium citrate and magnesium-alkali citrate as modulators of calcium oxalate crystallization in urine: observations in patients with recurrent idiopathic calcium urolithiasis

Abstract: The effects of magnesium (Mg) and citrate on the metastable limit of calcium oxalate (CaOx) solubility (synonym: tolerable oxalate TO) were examined in artificial urine and in postprandial urine of male patients with idiopathic calcium urolithiasis (ICU). In artificial urine increasing pH, Mg and citrate elevate TO, decrease CaOx supersaturation only marginally, but elevate considerably free citrate; the effect of Mg alone was small in comparison with citrate alone, and the effects of both substances appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 22 publications
0
48
0
2
Order By: Relevance
“…Our results suggest that high urinary magnesium can increase calciuria and potentially increase stone risk. Some have espoused the notion that magnesium is efficacious in preventing stone formation by binding or complexing oxalate in the bowel and urine, 26,27,40,41 by inhibiting calcium oxalate crystal formation, 26,42,43 and by increasing urinary citrate when given as alkali salt. 44 In vitro studies have shown that magnesium is an inhibitor of calcium oxalate crystal growth in artificial, rodent, and human urine but at supraphysiologic concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that high urinary magnesium can increase calciuria and potentially increase stone risk. Some have espoused the notion that magnesium is efficacious in preventing stone formation by binding or complexing oxalate in the bowel and urine, 26,27,40,41 by inhibiting calcium oxalate crystal formation, 26,42,43 and by increasing urinary citrate when given as alkali salt. 44 In vitro studies have shown that magnesium is an inhibitor of calcium oxalate crystal growth in artificial, rodent, and human urine but at supraphysiologic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…51 TRPV5 is critical in that process, and its deletion in the mouse leads to pronounced hypercalciuria. 43 TRPV5 is regulated by numerous calcitropic hormones but also by its own transported substrate. 52 As intracellular calcium concentration rises, TRPV5 open probability decreases drastically.…”
Section: Discussionmentioning
confidence: 99%
“…5 All ions studied used the CHARMM27 force field. 6,7 Force field parameters determined by Yesselman and associates 8 via MATCH were used for Ox 2 -and citrate (Cit 3 -), while those for phosphate (PO 4 3 -) and dihydrogen phosphate (H 2 PO 4 -) were determined using CHARMM general force field (CGenFF) 9 in the CHARMM program. The standard TIP3P potential model was used for water.…”
Section: Methodsmentioning
confidence: 99%
“…For systems 7 and 8, citrate was inserted to evaluate its effect on aggregates. Systems 9 and 10 were generated from systems 4 and 6 by replacing their PO 4 3 -ions with H 2 PO 4 -to model an acidic urine environment. This allows us to study how pH influences Ca 2 + -Ox 2 -aggregation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation